The enhancement of efficiency in e-recruitment system using semantic matching technique - นิลพฤกษ์ ปองพล; ขนานขาว รักษารัตน์ (Progress in Applied Science and Technology, 2015)
In the last ten years, global trend of the Internet access increasingly grows very fast. As a result, it significantly impacts on the changes of e-Recruitment process directly. However, finding the most suitable applicant is still very difficult and always challenges in a recruitment process. This research intends to study about the enhancement of efficiency in e-recruitment system using semantic matching technique. The Semantic Web technology, ontology knowledge base, and semantic matching technique are mainly used in this research in order to design the conceptual framework of the prototype system, design the prototype of ontology knowledge based, and improve the efficiency in matching process using the similarity and learning curve method. Moreover, Weight Sum Model (WSM) is also used to improve the efficiency in matching process. Finally, 10 sample data of applicants was tested on the proposed semantic matching, then the result expresses that the proposed semantic matching is more suitable than traditional terminological and similarity matching in case of distinguishing among applicants by calculated scores. The final scores from proposed semantic matching can nicely distinguish the differences among target applicants as well as the prototype system applying the Semantic Web technology can easily enable information sharing and reduce the duplicated information on the Internet because it is a standard. However, in future works, if we add more the good relationship of ontology or other factors, those can also enhance the efficiency in recruitment process to find more suitable person.